ANALISIS TUGAS AKHIR SKRIPSI MAHASISWA - Desy Tri Inayah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
The final thesis analysis of the student's thesis aims to obtain: 1) research design input, 2) in-depth information about the student thesis research profile, 3) various areas of expertise that are the focus of student research, 4) input on the research procedures undertaken by students, and 5) know the results and research products of students.This study uses 6 stages, namely: 1) Unitizing (uniting); 2) Sampling; 3) Recording / coding; 4) Reducing; 5) Inferring (taking conclusions), 6) Naratting (narration).The results of this study are: 1) 65% thesis abstract number of artistry there are 4, the formulation of the problem is less in accordance with the title (36%), the order of the conclusion of the thesis conclusion is less in accordance with the hypothesis and research questions (48%), while the composition of the thesis is coherent from the title, problem formulation, hypothesis / research questions, and conclusions there are only 36% of the total thesis there; 2) The existence of words that are less operational in the formulation of the problem (16%), the use of words that are less appropriate in the title (5%), the existence of the title of the thesis that is less appropriate to the field of expertise (5%).